Odpowiedź :
Odpowiedź:
a) x=-18
b) 4y=17/:4
y=4½
c)-7/9z=7/9 mnóżmy to przez -9/7
z=-1
d) mnożymy to przez - 6
u=-2
e) dzielimy to przez 12
y=-3
f) dzielimy to przez - 3
w=-1/18
g) a=0
h) dzielmy to przez - 3
b=-⅛
i) dzielimy to przez - 11
c=-8
Odpowiedź:
a) 1/9 x= - 2 /*9
x= -18
b) 4y= 17 /:4
y= 17/4
c) -7/9 z = 7/9 /*( - 9/7)
z= -1
d) - 1/6u= 1/3 /* (-6)
u= - 2
e) y * 12= - 36 /:12
y= - 3
f) - 3w = 1/6 /: (-3)
w= - 1/18
g) - 4a = 0 /: (-4)
a= 0
h) -3b = 3/8 /: (-3)
b= - 3/24
i) - 11c = 88 /: (-11)
c= -8
Liczę na naj. Pozdrawiam :D
Szczegółowe wyjaśnienie: